Phase-shift space vector pulse width modulation for nine-switch inverter - Jarutus,N. (2015)
© 2014 IEEE. In this paper, a phase-shift space vector modulation technique is proposed to control the dual-load of the nine-switch inverter. The proposed algorithm is based on a carrier-based space vector pulse width modulation (SVPWM) under the constant frequency (CF) and the variable frequency (VF) operation modes. The modulation signals are operated by without crossover to avoid the distortion of output voltages. The switching states can prevent the short through in the inverter leg. For the CF-mode, the modulation indices are identical and less than, or equal to 2/√3. Therefore, the sum of phase-shift angles is 0°. For the CF and VF modes, the displacement phase-shift angle is able to adjust from 0° to 360°, when the sum of modulation indices is less than, or equal to 2/√3. The proposed phase-shift SVPWM technique is verified by simulation results, showing good steady-state performance.